isoAmyl Propionate production by the integration of reaction/distillation operations (2014)
Abstract. This work studied the production of isoamyl propionate by the direct esterification of propionic acid with isoamyl alcohol, refined from the Colombian fuel-ethanol by-products, using the reactive distillation technology as a possible process solution. This, as way to increase the social-economic value of the fuel-ethanol industry of Colombia. For this objective, the analysis and modeling of Vapor-Liquid-Liquid (VLL) phase equilibrium of the sub-binary systems and the liquid esterification reaction kinetics heterogeneously catalyzed, were performed. Specifically for the phase equilibrium studies, VLL data were collected from existing reports in the open literature and phase equilibrium data generated for the missing binary systems, propionic acid-isoamyl propionate and isoamyl alcohol-isoamyl propionate (T-x-y data at 50.00, 101.33 and 150.00 kPa). For the kinetic study, experimental data were collected from batches of kinetic experiments for different reactant molar ratios (2:1, 1:1 and 1:2, acid to alcohol), different isothermal reaction temperatures (80, 100 and 120 C), and different loadings of Amberlyst® 70 as catalyst (0.8, 4.0 and 8.0 wt%). From the VLL and kinetics concluded models, the synthesis of a reaction-distillation operation was performed at steady state, using for the operation conceptual design the analysis of residue curve maps for subternary and the total quaternary systems, with and without chemical reaction, together with mathematical simulations in Aspen Plus® 7.3 chemical engineering software of reactive distillation models, based on equilibrium stage approach. Experimental evaluations of the possible concluded operation at steady state were carried out in a pilot scale reactive distillation column, validating the principal results of the operation modeled and concluded. The main conclusion of this work was that it is possible to produce isoamyl propionate by the direct esterification of propionic acid with refined isoamyl alcohol, with purities over 98% wt. and conversions of equimolar reactants mixtures around of 96%, in a single reactive distillation process operation.